2020
DOI: 10.1515/ntrev-2020-0053
|View full text |Cite
|
Sign up to set email alerts
|

Nanoengineering in biomedicine: Current development and future perspectives

Abstract: Recent advances in biomedicine largely rely on the development in nanoengineering. As the access to unique properties in biomaterials is not readily available from traditional techniques, the nanoengineering becomes an effective approach for research and development, by which the performance as well as the functionalities of biomaterials has been greatly improved and enriched. This review focuses on the main materials used in biomedicine, including metallic materials, polymers, and nanocomposites, as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 165 publications
(160 reference statements)
0
27
0
Order By: Relevance
“…Modern advancements in bioengineering mainly rely mostly on growth of Nano engineering [46]. Since exposure to specific characteristics in nanomaterials is not easily accessible through conventional approaches, Nano engineering is an efficient method to design and technology that has also significantly enhanced or strengthened both the efficiency as well as functionality of nanomaterials.…”
Section: Nano Engineering In Biomedicinementioning
confidence: 99%
See 2 more Smart Citations
“…Modern advancements in bioengineering mainly rely mostly on growth of Nano engineering [46]. Since exposure to specific characteristics in nanomaterials is not easily accessible through conventional approaches, Nano engineering is an efficient method to design and technology that has also significantly enhanced or strengthened both the efficiency as well as functionality of nanomaterials.…”
Section: Nano Engineering In Biomedicinementioning
confidence: 99%
“…It is observed that the potential to evaluate structural implementations with desirable characteristics as well as enhanced quality plays a significant part throughout the creation of futuristic structures that will offer innovative manufacturing long term possibilities in the domain of biomedicine. Nano engineering helps the modification for atomic as well as biological nanomaterials including its manufacture of nanostructures containing controlled operations [46].…”
Section: Nano Engineering In Biomedicinementioning
confidence: 99%
See 1 more Smart Citation
“…These natural biopolymers have significant advantages, such as long-term safety [21], desirable biocompatibility [22], and biodegradability [23]. However, the weak mechanical strength of most biopolymer-based scaffolds goes against the formation of artificial topographic structures [24]. Therefore, it is necessary to develop biocompatible materials with a stable topographic structure to meet current biomedical demands.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of current and potential nanotechnology application in the agrifood and biomedicine industry[49][50][51][52][53].…”
mentioning
confidence: 99%